2020
DOI: 10.1039/d0ra04815a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of violacein biosynthesis to enable a pigment-based whole-cell lead biosensor

Abstract: Genetically controlled violacein biosynthesis can enable a sensitive, visual, and qualitative biosensor for monitoring the presence of bioavailable lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Extensive studies have demonstrated that whole-cell biosensors could detect target molecules in polluted water (Yin et al, 2016 ; Maruthamuthu et al, 2017 ; Cui et al, 2018 ; Hui et al, 2020a ), soil extract (Rasmussen et al, 2000 ; Yoon et al, 2016a , b )(Rasmussen et al, 2000 ; Yoon et al, 2016a , b ), and milk (Kumar et al, 2017 ) by introducing these liquid samples to be tested into the culture system. Biotoxic molecules could be efficiently removed by whole-cell bioadsorbers from polluted water and soils (Wei et al, 2014 ; Maruthamuthu et al, 2017 ; Tang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have demonstrated that whole-cell biosensors could detect target molecules in polluted water (Yin et al, 2016 ; Maruthamuthu et al, 2017 ; Cui et al, 2018 ; Hui et al, 2020a ), soil extract (Rasmussen et al, 2000 ; Yoon et al, 2016a , b )(Rasmussen et al, 2000 ; Yoon et al, 2016a , b ), and milk (Kumar et al, 2017 ) by introducing these liquid samples to be tested into the culture system. Biotoxic molecules could be efficiently removed by whole-cell bioadsorbers from polluted water and soils (Wei et al, 2014 ; Maruthamuthu et al, 2017 ; Tang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the effects of reporters, optimization of detection conditions including the type of culture mediums, induction time and induction duration, was another important factor for enhanced sensitivity [ 13 , 16 , 36 ]. Although whole-cell biosensors responded to low concentration of heavy metal when lag-phase culture of biosensor cells was directly exposed to toxic metal [ 7 , 10 ], exponential phase biosensor cells could produce significantly stronger reporter signals including fluorescent protein, β-galactosidase, and pigment [ 13 , 35 , 37 , 38 ]. Furthermore, logarithmic phase bacterial cultures were usually induced to improve the expression amount of surface-displayed metal binding proteins [ 16 , 18 , 21 , 37 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a biosensor was constructed that is sensitive to high concentrations of Pb (II) compounds with pigmentation as an output signal. According to the mechanism indicated by the authors, violacein is formed as a result of the conversion of two molecules of endogenous L-tryptophan under the influence of five proteins, which are transcribed and translated as a single polycistronic unit under induction of Pb (II) [9].…”
Section: Introductionmentioning
confidence: 99%